Diversity and functional guild of understory birds in different types of forest in ulu Baram, Sarawak - Attiqqah Fazillah, Sapian; Jayasilan, Mohd-Azlan; Khatijah, Ismail; Pang, Sing Tyan; Rahah, Mohd Yakup; Mohd Hasri Al-Hafiz, Haba; Isa, Sait; Andrew Alek, Tuen (Malaysian Society of Applied Biology, 2018)
The difference on diversity of understory and functional guild of understory birds were examined in three types of forest relatively undisturbed primary, secondary and agro forest in Ulu Baram, Sarawak. A total of 64 mist nets were set up in each forest type for four days. A total of 140 individuals representing 38 species were caught in primary forest, 201 individuals (50 species) in secondary forest and 216 individuals (47 species) in agro forest. Shannon-Wiener Diversity Index showed that secondary forest has the highest bird diversity (H’ = 3.518) followed by agro (3.312) and primary forest (3.249). The relative abundance of the insectivores was the highest in primary forest, frugivores, granivores and nectarivores were highest in the agro forest while the omnivore guild dominated the secondary forest. The granivores, frugivores and nectarivores were higher in agro forest suggesting that this forest provide resources for the persistence of these species. The results of this study showed the feeding guild and diversity of understorey birds were influenced by the habitat type.